Measles Vaccination in Presence of Measles Antibody May Enhance Child Survival - Benn, Christine S.; Martins, Cesário L.; Andersen, Andreas; Fisker, Ane B.; Whittle, Hilton C.; Aaby, Peter (Frontiers in Pediatrics, 2020)
Background In trials of early two-dose measles vaccination (MV), with the first dose being given before 9 months of age, vaccination in the presence of maternal antibody reduced mortality two-to-three-fold compared with MV in the presence of no measles antibody. We tested this finding in two historical studies in which the children had received one dose of MV. Methods We used data from a surveillance study of seroconversion after standard-titre MV (Schwarz strain) (Study 1) and a trial of early medium-titre MV (Edmonston-Zagreb strain) in which a pre-vaccination blood sample had been collected (Study 2). Both studies had control children, who were enrolled under similar conditions, but did not receive effective MV. Study 1 was a natural experiment where all children measles vaccinated during one month did not seroconvert and had therefore received an ineffective vaccine. In Study 2, the controls were randomised to an inactivated polio vaccine (IPV). We compared mortality for children with undetectable levels of measles antibody (<31.25 mIU) at baseline with children with detectable levels (>=31.25 mIU). Results In both studies, children who were measles vaccinated in the presence of measles antibody had lower mortality compared with children who were measles vaccinated in presence of no measles antibody, the combined mortality rate ratio (MRR) being 0.51 (0.27-0.96). In the control groups, a detectable level of measles antibody versus an undetectable level was not associated with lower mortality, the MRR being 1.40 (0.31-6.38). Conclusion The results supported previous findings: Measles vaccination in the presence of measles antibody had beneficial effects on child survival. Since maternal antibody levels are declining, it may be time to consider giving MV earlier and/or to provide MV to adolescent girls to boost antibody levels.